PENINGKATAN KEMAMPUAN BERPIKIR KRITIS SISWA MELALUI MODEL PEMBELAJARAN KOOPERATIF THINK PAIR SHARE DI KELAS X SMA NEGERI 1 PADANG BOLAK - Ade Isma Hasibuan; Abubakar Abubakar; Fatma Suryani Harahap (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2018)
The problem of this research is the low of the student’ ability critical thinkig and the result of student study of SMA Negeri 1 Padang Bolak in class ten. The goal of this research is to make the critical thinking of the student  of the student better and to make better the result of their study is chemistry by using cooperatif studying think pair share. The tool to collect the data is test of ability in critical thinking questioner of critical thinking, paper of student activity and also teacher work. The observation kind of research is class action research (PTK). The result of the student study by using studying method of student cooperatif think pair share in the class of ten and according to the result of the student ability in critical thinking in the first siclus is 16  the student pass the tes and the second siclus about 25 the student pass the test from 30 student follow student tes. The result questioner of critical thinking first siclus is enough and second siclus is very good. The result activity observation student has increased as well as the teacher performance observation that has increased. From the research we kow that there is the growth i the questioner of student thinking thinking ability, student activities and the teachers ability in using think pair  pair share cooperative studying model in class ten of Mia-4 SMA Negeri 1 Padang Bolak. So, this model can be used i chemistry study and others.